A new method for analysis of constant-temperature thermal response tests. (March 2019) - Aydin, Murat; Onur, Mustafa; Sisman, Altug
Highlights: An analytical model is developed for analyzing constant-temperature thermal tests. Thermal conductivity of ground is obtained without estimating the heat capacity. The model is validated with numerical model and applied to experimental results. Abstract: In this study, a new analysis method is proposed for estimating thermal conductivity of a ground by using the constant-temperature thermal response test data. The new method is based on an analytical solution of heat transfer rate per unit borehole length by using the Laplace transformation for constant-temperature thermal response tests. Its advantage is that it allows one to estimate thermal conductivity directly from the slope of the logarithmic time dependency of inverse unit-heat-transfer rate value without making an estimation of volumetric heat capacity. The method has been verified by using a numerical model and applied to different experimental data based on different test temperatures and compared with the classical thermal response test method. The results show that the proposed method reliably and effectively estimates thermal conductivity of ground.